2020
DOI: 10.3390/ijms21103648
|View full text |Cite
|
Sign up to set email alerts
|

SCREENED: A Multistage Model of Thyroid Gland Function for Screening Endocrine-Disrupting Chemicals in a Biologically Sex-Specific Manner

Abstract: Endocrine disruptors (EDs) are chemicals that contribute to health problems by interfering with the physiological production and target effects of hormones, with proven impacts on a number of endocrine systems including the thyroid gland. Exposure to EDs has also been associated with impairment of the reproductive system and incidence in occurrence of obesity, type 2 diabetes, and cardiovascular diseases during ageing. SCREENED aims at developing in vitro assays based on rodent and human thyroid cells organize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 126 publications
0
11
0
Order By: Relevance
“…This model opens a new window on the morphogenetic processes and gene regulatory networks associated with thyroid development. In addition, it could be used as a model to study the role of newly identified variants in causing congenital hypothyroidism and to test the toxic effects of many compounds to which we are constantly exposed in our daily life, in particular endocrine disruptors 76 , an emerging challenge in thyroid pathophysiology. Although this model still needs improvement before it becomes therapeutically applicable, it provides a proof of concept that generating autologous human thyroid tissue to maintain TH levels is within reach.…”
Section: Discussionmentioning
confidence: 99%
“…This model opens a new window on the morphogenetic processes and gene regulatory networks associated with thyroid development. In addition, it could be used as a model to study the role of newly identified variants in causing congenital hypothyroidism and to test the toxic effects of many compounds to which we are constantly exposed in our daily life, in particular endocrine disruptors 76 , an emerging challenge in thyroid pathophysiology. Although this model still needs improvement before it becomes therapeutically applicable, it provides a proof of concept that generating autologous human thyroid tissue to maintain TH levels is within reach.…”
Section: Discussionmentioning
confidence: 99%
“…For these chemicals, the GOLIATH, OBERON and EDCMET consortia aim to develop assays targeting the main nuclear receptors and tissues involved in metabolic diseases ( Audouze et al, 2020 ; Küblbeck et al, 2020 ; Legler et al, 2020 ). Although few test guidelines exist for thyroid disruption (EATS modality), no validated in vitro alternatives exist and the ATHENA, ERGO and SCREENED projects are establishing methods on different modes of thyroid disruption using advanced cell cultures and alternative animal models ( Holbech et al, 2020 ; Kortenkamp et al, 2020 ; Moroni et al, 2020 ). The ENDpoiNTs project will aid in the understanding of the mode of action (MoA) of EDCs on the neuroendocrine axis by establishing new methodologies ( Lupu et al, 2020 ), whereas the FREIA project addresses the lack of test methods for female reproduction ( Duursen et al, 2020 ).…”
Section: Current International Undertakings For the Non-eatsmentioning
confidence: 99%
“…EDCs can widely affect this process and thyroid disruption can occur at any level of the HPT axis including thyroid hormones synthesis, release, transport, metabolism, and action on target tissues [ 2 , 245 , 246 ]. Clinical studies are still few and controversial and three projects within the EURION [ 28 ] are focusing on improvement of testing strategies for thyroid hormone EDCs: ATHENA [ 247 ], ERGO [ 248 ], and SCREENED [ 249 ].…”
Section: Edcs and Endocrine Diseases—evidence In Humansmentioning
confidence: 99%